A tool for laboratory investigations of radial stress in steel cold flex processes - Plančak, Miroslav (Journal of Production Engineering, 1984)
Knowledge of contact stresses in hyad extrusion is extremely important not only for die design but also for theoretical analysis of the process. Given the limitations of theoretical determination of contact stresses, a number of experimental methods have been developed. One of the most accurate experimental methods is the measuring probe method. Based on this method, a laboratory device for measuring the radial contact stress on the die wall during the extrusion process has been developed and implemented, and is presented in this paper. The results of the measurement of the radial stress are also presented.